Orthodontic Space Closure of a Missing Maxillary Lateral Incisor Followed by Canine Lateralization - Sanjay Prasad Gupta; Shristi Rauniyar (Hindawi Limited, 2020)
Maxillary lateral incisor agenesis is the most prevalent developmental dental anomaly. The management of missing lateral incisor was either closure using canine as substitution or creation of space orthodontically for prosthetic replacement. A careful diagnosis and treatment plan are deemed essential to address the patient's needs as the spacing is present in the esthetic region. Such problem is very challenging for orthodontists, prosthodontists, and general practitioners. This case report describes the orthodontic management of a 22-year-old adult female patient with missing upper left lateral incisor tooth and upper anterior spacing by closing the space with canine lateralization and reshaping to simulate it with the lateral incisor. However, some modifications in the treatment mechanics are crucial to achieve the optimal esthetic and to improve the occlusion. Space closure with canine lateralization option seems less invasive, treatment can be completed relatively in a short period of time, and its adaptation with the facial changes throughout life without having artificial prosthesis provided other factors favoring for this option.